Exploring the Use of the Numbered Heads Together (NHT) Cooperative Learning Method in Enhancing Arabic Speaking Skills at Integrated Islamic Junior High School Pekanbaru - Nurjannah Harahap; Hakmi Wahyudi (Universitas Islam Negeri Palopo, 2026)
This study aims to explore the implementation, perceived impact, and challenges of the Numbered Heads Together (NHT) cooperative learning method in Arabic speaking learning among eighth-grade students at Integrated Islamic Junior High School Pekanbaru. This study employs a qualitative approach using field research. Data were collected through observation, interviews, and documentation involving the Arabic language teacher, the school principal, and eighth-grade students at Integrated Islamic Junior High School Pekanbaru. The results indicate that the implementation of the NHT cooperative learning method effectively enhances students’ engagement, confidence, and self-assurance in speaking Arabic. Students became more active in discussions, more prepared to provide answers, and more confident in expressing their opinions due to individual responsibilities within the group. Additionally, the learning environment became more interactive, communicative, and student-centered. The NHT method also helped students enrich their vocabulary, improve sentence structure, and practice speaking fluency through group collaboration. However, this study also identified several challenges, such as limited vocabulary, pronunciation difficulties, and anxiety among some students when speaking. Therefore, teacher guidance, continuous practice, and vocabulary reinforcement are necessary to optimize learning outcomes. Thus, the Numbered Heads Together (NHT) cooperative learning method is effective as an alternative learning strategy to improve students’ Arabic speaking skills.